2020
DOI: 10.1007/s10494-020-00147-9
|View full text |Cite
|
Sign up to set email alerts
|

Near-Wall Flame and Flow Measurements in an Optically Accessible SI Engine

Abstract: Near-wall processes in internal combustion engines strongly affect heat transfer and pollutant emissions. With continuously improving capabilities to model near-wall processes, the demand for corresponding measurements increases. To obtain an in-depth understanding of the near-wall processes within spark-ignition engines, flame distributions and flow fields were measured simultaneously near the piston surface of an optically accessible engine operating with homogeneous, stoichiometric isooctane-air mixtures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Rigorous experimental research is required to provide detailed data for the development of accurate models of engine phenomena and the reduction of CCVs. 1 Over the last decades, advancements in laser and imaging technology have enabled IC engine research to expand to high-speed, crank angle-resolved 24 and high-resolution boundary layer velocity and fuel film measurements 58 as well as multi-parameter measurements to examine the propagation of the early flame kernel. 9 With the increase in technology, also comes the ability of generating better statistics for flow and flame data obtained from advanced laser diagnostics in IC engines and the subsequent use of machine learning (ML)-based processing and analysis techniques to better understand the phenomena involved in engine CCV.…”
Section: Introductionmentioning
confidence: 99%
“…Rigorous experimental research is required to provide detailed data for the development of accurate models of engine phenomena and the reduction of CCVs. 1 Over the last decades, advancements in laser and imaging technology have enabled IC engine research to expand to high-speed, crank angle-resolved 24 and high-resolution boundary layer velocity and fuel film measurements 58 as well as multi-parameter measurements to examine the propagation of the early flame kernel. 9 With the increase in technology, also comes the ability of generating better statistics for flow and flame data obtained from advanced laser diagnostics in IC engines and the subsequent use of machine learning (ML)-based processing and analysis techniques to better understand the phenomena involved in engine CCV.…”
Section: Introductionmentioning
confidence: 99%
“…The advection speed decreases slightly during the compression stroke, and then, it increases rapidly. Schmidt et al 26 observed flow acceleration in front of a flame in an optically accessible engine, and thus, it is assumed that the combustion provoked this acceleration. The cyclic variability evaluated in standard deviation is strong, whereas it attenuates after the combustion.…”
Section: Resultsmentioning
confidence: 99%
“…PTV was calculated for a particle size range from 1 to 8 pixels and with a correlation window size of 8 pixels. PTV vectors were converted to a structured pixels 2 grid, as performed in previous boundary layer studies (Ding et al 2019 ; Schmidt et al 2021 ). This step was performed in DaVis using a “simple averaging / strong filter” scheme in DaVis, which provided the most reliable PTV results.…”
Section: Application To Experimental Datamentioning
confidence: 99%
“…Optical flow is a method often referred to in literature as dense motion estimation, i.e., a velocity vector is calculated for every pixel in a digital image. Application of optical flow velocimetry (OFV) techniques have previously demonstrated increased accuracy and resolution over conventional correlation-based methods (Yuan et al 2007 ; Ruhnau et al 2007 ; Corpetti et al 2006 ; Héas et al 2012 ; Dérian et al 2013 ; Kadri-Harouna et al 2013 ; Schmidt and Sutton 2020 ; Schmidt et al 2021a , b ). Such studies have primarily focused on synthetic and experimental test cases involving analytical flows, isotropic turbulence and free shear flows.…”
Section: Introductionmentioning
confidence: 99%